Leisure Shopping and Fashion Tour: New Elements of the Marche Tourist Offer - Enrico Nicosia (Bollettino della Società Geografica Italiana, 2021)
In the last decade, the Italian region Marche has consolidated a respectable position in the national and international panorama of tourist destinations. A region, that in building its territorial brand, has used its peculiar mix of past traditions and modern innovations to offer tourists a complex territorial product. This blend of natural, cultural and historical resources succeeds in appealing and attracting even the most demanding visitor. Purchasing goods during a holiday has always been a significant activity of the tourism macro- industry, both from the economical and experiential point of view. Within the variable framework of the tourism market, where destinations and operators have to adapt and enhance their offer to better attract their targets, analyzing how shopping could be a primary, secondary or ancillary reason for traveling, is a matter of crucial interest. Such travels can require short movements, typically one-day or week-end trips, but can also be characterized by a longer duration where other experiences, besides shopping, are combined. This phenomenon and its demand have historically involved Italy, a country that can rely on a diversified and high-quality offer that valorizes and combines traditions, expertise and local products along with the offer of big international brands. Among the various itineraries offered, the ones that connect places of tradition, industriousness and local craftsmanship to areas designated to prestigious fashion brands and clothing outlets, are of particular interest. The incorporation of shopping activities within a vivid framework of traditional entrepreneurial businesses is both a pleasant and advantageous experience. It represents the opportunity for a renewed exploration of the area and the rediscovery of the best local production companies. The objective of this work, through a field survey and interviews with tourists, entrepreneurs and workers of these sectors, is to investigate the phenomenon in its territorial consistency in order to understand if there is a substantial cause and effect relationship between the two sectors.